ANALISA PREDIKSI FINANCIAL DISTRESS DENGAN METODE GROVER O-SCORE PADA PT TRI BANYAN TIRTA TBK PADA TAHUN 2016-2020 - Irine Fauziah Putri; Trisnia Widuri; Zaenul Muttaqien (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The development of globalization is progressing very rapidly and is expanding, this causes companies that are old enough to be difficult to compete with experienced companies. So the company can experience financial distress that can lead to bankruptcy. One of the companies that are threatened with financial distress is PT Tri Banyan Tirta Tbk in 2016-2020. The model used in this study is the Grover O-Score Model, which is a model made by assessing and redesigning the Altman Z-Score. The purpose of this study was to explain the prediction of financial distress using the Grover O-Score Method at PT Tri Banyan Tirta Tbk. The results of the study state in 2016 the company experienced non- distress with classification of 0.024, in 2017 the company experienced non- distress with classification of -0,026, in 2018 the company experienced financial distress with classification of -0.0.100, in 2019 the company experienced financial distress with classification of 0.005, in 2020 the company experienced financial distress with classification of -0.002.